2023
DOI: 10.1029/2023ja031354
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Propagation and Effects of Gravity Waves Generated by Tonga Volcano Eruption in the Thermosphere and Ionosphere Using Nested‐Grid TIEGCM

Abstract: Atmospheric gravity waves (GWs) play an important role in energy and momentum coupling from the lower to the upper atmosphere (Fritts, 1984;Fritts & Alexander, 2003). GW sources are manifold, including topography, convection, wind shear, geostrophic adjustment, body forcing, and wave-wave interactions . GWs can propagate to the mesosphere and thermosphere, which leads to changes in the energy and momentum budget (Alexander et al., 2010;Vadas & Fritts, 2005). GW impacts manifest in the ionospheric E and F regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
(78 reference statements)
3
5
0
Order By: Relevance
“…In Miyoshi and Shinagawa (2023), GAIA was used to study atmospheric and ionospheric perturbations triggered by the 2022 Hunga-Tonga volcanic eruption. Lamb waves and gravity waves driven by the eruption and ionospheric variations associated with those waves were reproduced, which are roughly consistent with other simulation studies of the atmosphere-ionosphere variations in the eruption (Liu et al 2023a;Wu et al 2023;Vadas et al 2023b;Huba et al 2023).…”
Section: Gaia Modelsupporting
confidence: 89%
See 2 more Smart Citations
“…In Miyoshi and Shinagawa (2023), GAIA was used to study atmospheric and ionospheric perturbations triggered by the 2022 Hunga-Tonga volcanic eruption. Lamb waves and gravity waves driven by the eruption and ionospheric variations associated with those waves were reproduced, which are roughly consistent with other simulation studies of the atmosphere-ionosphere variations in the eruption (Liu et al 2023a;Wu et al 2023;Vadas et al 2023b;Huba et al 2023).…”
Section: Gaia Modelsupporting
confidence: 89%
“…Recent numerical simulation studies of the atmospheric variation driven by the HTHH volcano have successfully reproduced the Lamb waves and Pekeris waves (L'1 mode of the Lamb waves) (e.g., Watanabe et al 2022;). The ionosphere-atmosphere coupled models have indicated that Lamb waves and/or gravity waves triggered by the eruption generate TIDs, which propagate concentrically from HTHH (Wu et al 2023;Liu et al 2023a;Miyoshi and Shinagawa 2023;Vadas et al 2023b). As for the large-scale variations in the ionosphere and thermosphere, our simulation result is basically the same as those studies.…”
Section: Cause Of Tidssupporting
confidence: 62%
See 1 more Smart Citation
“…Recent numerical simulation studies of the atmospheric variation driven by the HTHH volcano have successfully reproduced the Lamb waves and Pekeris waves (L' 1 mode of the Lamb waves) (e.g., Watanabe et al 2022;Liu et al 2023a, b). The ionosphere-atmosphere coupled models have indicated that Lamb waves and/or gravity waves triggered by the eruption generate TIDs, which propagate concentrically from HTHH (Wu et al 2023;Liu et al 2023a;Miyoshi and Shinagawa 2023;Vadas et al 2023b). As for the large-scale variations in the ionosphere and thermosphere, our simulation result is basically the same as those studies.…”
Section: Cause Of Tidssupporting
confidence: 62%
“…Although our simulation reproduced the concentric TIDs directly propagating from HTHH, it could not reproduce the observed concentric TIDs in geomagnetic conjugate region that are related to the directly propagating TIDs (e.g., Shinbori et al 2022;Lin et al 2022). Other simulation studies also could not clearly reproduce concentric TID pattern in the magnetic conjugate region (Vadas et al 2023b;Wu et al 2023;Liu et al 2023a;Miyoshi and Shinagawa 2023). the concentric electric field in both hemispheres collide with each other, forming an X-type electric field structure at the equatorial region (Fig.…”
Section: Ionospheric Variationsmentioning
confidence: 68%